Behavioral and psychosocial factors related to mental distress among medical students - Carlos, Kathleen M.; Ahmadi, Hedyeh; Uban, Kristina A.; Riis, Jenna L. (Frontiers in Public Health, 2023)
Introduction Physicians die by suicide at rates higher than the general population, with the increased risk beginning in medical school. To better understand why, this study examined the prevalence of mental distress (e.g., depressive symptoms, suicide risk) and behavioral and psychosocial risk factors for distress, as well as the associations between mental distress and risk factors among a sample of medical students in a pre-COVID-19-era. Methods Students enrolled in a large California medical school in 2018-19 (N=134; 52% female) completed questionnaires assessing sociodemographic characteristics, depression and suicide family history, health behaviors, and psychosocial well-being. Assessment scores indexing mental distress (e.g., depressive symptoms, thoughts of suicide in the past 12 months, suicide risk, and history of suicidality) and risk factors (e.g., stress, subjective sleep quality, alcohol use, impostor feelings, and bill payment difficulty) were compared across biological sex using chi-squared tests, and associations between mental distress and risk factors were determined through logistic regression. Results Elevated mental distress indicators were observed relative to the general public, (e.g., 16% positive depression screen, 17% thought about suicide in previous 12 months, 10% positive suicide risk screen, 34% history of suicidality), as well as elevated risk factors (e.g., 55% moderate or high stress, 95% at least moderate impostor feelings, 59% poor sleep quality, 50% screened positive for hazardous drinking (more likely in females), 25% difficulty paying bills). A positive depression screen was associated with higher stress, higher impostor feelings, poorer sleep quality, and difficulty paying bills. Suicidal ideation in the previous 12 months, suicide risk, and a history of suicidality were independently associated with higher levels of impostor feelings. Discussion Higher scores on assessments of depressive symptoms and suicidal thoughts and behaviors were related with several individual-level and potentially modifiable risk factors (e.g., stress, impostor feelings, sleep quality, bill payment difficulties). Future research is needed to inform customized screening and resources for the well-being of the medical community. However, it is likely that modification of individual-level risk factors is limited by the larger medical culture and systems, suggesting that successful interventions to mitigate suicide risk for medical providers needs to address multiple socio-ecological levels.